2007
DOI: 10.1021/bc070039u
|View full text |Cite
|
Sign up to set email alerts
|

Aequorin-Based Homogeneous Cortisol Immunoassay for Analysis of Saliva Samples

Abstract: Homogeneous assays are attractive because they are performed in only one phase, namely, the liquid phase, and thus, they do not require separation of phases as their heterogeneous counterparts do. As opposed to heterogeneous assays, the signal generation in a homogeneous assay is a direct result of analyte binding, which allows the multiple washing and incubation steps required in an indirect heterogeneous assay format to be eliminated. Moreover, homogeneous assays are usually fast and amenable to miniaturizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
(28 reference statements)
1
11
0
Order By: Relevance
“…To apply the method for saliva sample detection, saliva sample was collected from healthy subject in the morning and the method measure the salivary glucose level (SGL) of 0.08 mM (n=3). The result obtained here was in agreement with other methods reported in relevant literature [9,42], indicating that this work holds potential application for an useful noninvasive glucose detection method by monitoring salivary glucose level.…”
Section: Analytical Applicationsupporting
confidence: 91%
See 1 more Smart Citation
“…To apply the method for saliva sample detection, saliva sample was collected from healthy subject in the morning and the method measure the salivary glucose level (SGL) of 0.08 mM (n=3). The result obtained here was in agreement with other methods reported in relevant literature [9,42], indicating that this work holds potential application for an useful noninvasive glucose detection method by monitoring salivary glucose level.…”
Section: Analytical Applicationsupporting
confidence: 91%
“…As is well-known, the salivary sample is convenient for collecting and pretreatment. Salivary glucose level (SGL) has been reported in significant concentrations, which is correlated with blood glucose level (BGL) [8,9]. Hence, numerous efforts have been devoted to develop nonenzymatic glucose sensors with high sensitivity and low detection limit [10].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the measurement signal is directly altered upon binding of analyte molecules, which allows minimizing or even completely skipping sample preparation procedures. 10 Another advantage of homogeneous assays is their faster transition to equilibrium due to the three dimensional diffusion of both the analyte molecule as well as the capture probe.…”
Section: Nanoparticle Biosensormentioning
confidence: 99%
“…The optimized homogeneous immunoassay has a detection limit of 1 10 -10 M of free cortisol. This BLI system proved to be a useful tool to measure the concentration of free cortial in saliva for diagnosis of a veriety of diseases caused by abnormal cortisol levels [28]. So et al recently reported a strategy for imaging discrete mRNAs with a transsplicing ribozyme from Tetrahymena thermophilia.…”
Section: Luciferase Fused Proteins For Imagingmentioning
confidence: 99%